2011
DOI: 10.1063/1.3601113
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile bipolar resistive switching in Au/BiFeO3/Pt

Abstract: Nonvolatile bipolar resistive switching has been observed in an Au/BiFeO3/Pt structure, where a Schottky contact and a quasi-Ohmic contact were formed at the Au/BiFeO3 and BiFeO3/Pt interface, respectively. By changing the polarity of the external voltage, the Au/BiFeO3/Pt is switched between two stable resistance states without an electroforming process. The resistance ratio is larger than two orders of magnitude. The resistive switching is understood by the electric field - induced carriers trapping and detr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
87
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 23 publications
3
87
0
Order By: Relevance
“…More Fe 2+ ions imply more oxygen vacancies and a larger leakage current density. [31] In addition, the reduction of the leakage current results from the structural transformation with Ho-doped, Mndoped and (Ho, Mn) co-doped thin films, as discussed above. The leakage current density of the pure BiFeO 3 thin films is larger than that of the BHFO, BFMO, and BHFMO films when it exhibits a rhombohedral structure, which indicates that the rhombohedral structure is closely related to the higher leakage current density.…”
Section: Resultsmentioning
confidence: 93%
“…More Fe 2+ ions imply more oxygen vacancies and a larger leakage current density. [31] In addition, the reduction of the leakage current results from the structural transformation with Ho-doped, Mndoped and (Ho, Mn) co-doped thin films, as discussed above. The leakage current density of the pure BiFeO 3 thin films is larger than that of the BHFO, BFMO, and BHFMO films when it exhibits a rhombohedral structure, which indicates that the rhombohedral structure is closely related to the higher leakage current density.…”
Section: Resultsmentioning
confidence: 93%
“…4,5 Multiferroic BiFeO 3 6,7 is an example of a material which is known in the two aforementioned fields. It exhibits bipolar resistive switching 8,9 and as a multiferroic material, it possesses ferroelectric DWs. It was shown that electrical properties of DWs in BiFeO 3 differ from those of bulk material.…”
Section: Introductionmentioning
confidence: 99%
“…While the top interfaces did not suffer annealing during the fabrication process, it is reported theoretically and experimentally that the annealing has the defect-healing effect [24,25]. And, the interface characteristics and resistance switching effect dependent on the annealing have been also investigated [3,26]. Therefore, the asymmetric interface characteristic between top and bottom Pt/MgZnO interfaces is believed in the present study, especially the defect concentration.…”
mentioning
confidence: 88%